Game Based Education : Pengenalan Peristiwa Sejarah Permesta di Minahasa - Pangau, Louis Y.D.; Kaunang, Sumenge T.G.; Lumenta, Arie S.M. (Universitas Sam Ratulangi, 2019)
Abstract - The history of Permesta in Minahasa is the local content of the Minahasa region. The development of games now has been so advanced, including Game based education that can encourage learning. This study aims to design a Game based education which will be a medium for storytelling learning that explains the historical events of Permesta. From the results of the evaluation the research can help and improve understanding of the material and attract interest and also become a place to introduce local content about the history of Permesta to the general public especially the younger generation.Keywords : Education, Game, History, Minahasa, PermestaÂ Abstrak â€“ Peristiwa sejarah Permesta di Minahasa merupakan konten lokal daerah Minahasa. Perkembangan game sekarang telah begitu maju, termasuk Game based education yang dapat mendorong pembelajaran. Penelitian ini bertujuan untuk merancangÂ Game based education yang akan menjadi media untuk pembelajaran dengan storytelling yang menjelaskan tentang peristiwa sejarah Permesta. Dari hasil evaluasi penelitian dapat membantu dan meningkatkan pemahaman materi serta menarik minat dan juga menjadi tempat untuk memperkenalkan konten lokal tentang sejarah Permesta kepada masyarakat umum terlebih khusus generasi muda.Kata kunci : Edukasi, Game, Minahasa, Permesta, Sejarah